DETERMINATION OF THE OPTIMUM CONDITIONS FOR UREASE INHIBITTION EXTRACTED FROM SOME LOCAL PLANTS - & et al., Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
In the current study, four types of plants commonly used namely Soybean, chickpea, bean, pea were obtained and screened for urease activity, among this plants, chickpea was chosen with maximum enzymatic activity, and it had the highest productivity of urease enzyme (1243 U/mg protein). Also sodium acetate buffer (0.2 M, pH 5.0) was chosen as a best extraction buffer with specific activity 1460 U/mg protein. The optimum extraction ratio represented by 1:8 (w:v) after 15 min, it was given 1988 U/mg protein. As well as four types of plants include garlic, red onion, green onion and cabbage were used to select the optimum plant material that inhibited urease enzyme. Cabbage was chosen, it had the highest inhibition activity of the enzyme (41%). Also tris buffer (0.2 M, pH 9) was selected as a best extraction buffer of plants inhibitor with inhibition activity 80%. The optimum extraction ratio represented by 1:8 (w:v) after 60 min, it was given 86% enzyme inhibition activity.